Item analysis of the ‘My Use of Interpersonal Skills Inventory’ - ŞİRİN, AHMET (My University, 1995)
A 32-item inventory was designed to provide data concerning the extent to which training in interpersonal and counselling skills was applied by educators in their professional and personal lives. An item analysis of the responses of 82 experienced educators was carried out on three testings completed before, soon after and one year following a training skills course. The item analysis revealed a high level of internal coherence for the inventory, indicating that improvement on any skill was related to improvement in the others. Correlations between the three applications of the inventory indicate an acceptable level of test-retest reliability. Apart from a clear face validity, data are reported confirming that interpersonal and counselling skills reported in the inventory are being applied in terms of reports of specific incidents. © 1995 Careers Research and Advisory Centre